2015
DOI: 10.2298/pif1502091m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salicylic acid elicitor against aphids on wheat and detection of infestation using infrared thermal imaging technique in Ismailia, Egypt

Abstract: SUmmARyWheat (Triticum sativum L.) is one of the most important cereal crops in Egypt. Insect pests, such as aphids, are major threats in terms of yield reduction. Induced resistance in wheat using salicylic acid as a foliar application was tested on the farm of the Faculty of Agriculture, Suez Canal University during 2012/2013 and 2013/2014 seasons. Three wheat cultivars, Gemeza 9, Sakha 93 and Giza 168, were sprayed three times with two concentrations of salicylic acid (SA), 200 mg/l and 100 mg/l, after earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
4
8
0
Order By: Relevance
“…The second season was the opposite of the first season. These results are in agreement with Mahmoud and Mahfouz (2015) results that revealed the foliar spray application of humic acid and salicylic acid reduced the As soon as (Pettersson et al, (1994) reported that cereal crops treated with a slow release formulation of methyl salicylate had been avoided by many insects, (Pickett et al, 2006) showed that salicylic acid caused a reduction in aphid population within five weeks after application.…”
Section: I13-tetranychus Urticaesupporting
confidence: 89%
“…The second season was the opposite of the first season. These results are in agreement with Mahmoud and Mahfouz (2015) results that revealed the foliar spray application of humic acid and salicylic acid reduced the As soon as (Pettersson et al, (1994) reported that cereal crops treated with a slow release formulation of methyl salicylate had been avoided by many insects, (Pickett et al, 2006) showed that salicylic acid caused a reduction in aphid population within five weeks after application.…”
Section: I13-tetranychus Urticaesupporting
confidence: 89%
“…Additionally, it has been revealed that lead causes an increase in endogenous free SA levels in all organs of Zygophyllum fabago [ 57 ]. The application of SA on wheat induced plant resistance to aphids [ 58 ]. El-Khawas [ 59 ] reported that priming plants with SA induced resistance of crop plants against herbivores, showing it to be successful in Pisum sativum against the leafminer Liriomyza trifolii .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, analysis of variance showed that nymphal developmental time was prolonged in plants treated with PeBL1 as compared to control. Also at lower temperature (16 • C), maximum nymphal development time was observed, confirming that an increase of one degree in temperature affects the insect's life cycle to become shorter [50]. Further studies are required to understand the underlying mechanism induced by PeBL1 in tomato plants, in particular, concerning its effect on fecundity and nymphal development time.…”
Section: Discussionmentioning
confidence: 75%